Sosialisasi Penguatan Kesadaran Masyarakat Terhadap Dampak Negatif Pernikahan Dini Dalam Perspektif Agama Hindu - Yanti, Ni Nengah Meistri; Sukendri, Nengah; Wiguna, Ida Bagus Alit Arta; Andari, Ida Ayu Made Yuni (IAHN Gde Pudja Mataram, 2024)
Early marriage is a social phenomenon that is still prevalent in many parts of the world, including Indonesia, with significant negative impacts on the health, education, and psychosocial well-being of individuals and communities. From a Hindu perspective, early marriage is not considered ideal as it contradicts the teachings on the importance of studying at a young age (brahmancari) before entering the household stage (grhasta). The practice of early marriage is often influenced by tradition, social pressure, and economic conditions, and has adverse effects on physical and mental health, as well as inhibiting the moral and psychosocial development of adolescents. This research uses communication methods through socialization and interactive discussions in Oman Nyambu Hamlet to raise community awareness about the dangers of early marriage. The results showed that socialization and legal and religious counseling are essential to increase community knowledge about the negative impacts of early marriage. These activities involve education and interactive discussions that help the community, especially teenagers and parents, understand the importance of delaying marriage until they reach emotional and mental maturity. Efforts to strengthen this awareness are expected to reduce the number of early marriages and improve the quality of life of the community. Thus, strengthening public awareness of the negative impact of early marriage in the Hindu perspective must continue to be promoted through various education and counseling programs. Only with high awareness and a good understanding of the importance of the brahmancari period, people can prepare themselves properly for life.